2021
DOI: 10.3390/ijms221910721
|View full text |Cite
|
Sign up to set email alerts
|

The NLRP3 Inflammasome: Relevance in Solid Organ Transplantation

Abstract: The NOD, LRR, and pyrin domain-containing 3 (NLRP3) protein has been established as a central component of the inflammasome and regulates the inflammatory response to a myriad of environmental, microbial, and endogenous danger stimuli. Assembly of the NLRP3 inflammasome results in the cleavage and activation of caspase-1, in turn causing release of the pro-inflammatory interleukins 1-beta and 18. This activation response, while crucial to coordinated innate immune defense, can be aberrantly activated by the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 122 publications
0
8
0
Order By: Relevance
“…Cell apoptosis-induced activation of inflammasomes is associated with cardiac allograft rejection ( 67 ). Caspase-1 activation is triggered by the assembly of inflammasome complexes, particularly Nlrp3, which function as sensors for ‘danger’ molecules or non-self signals, such as donor-derived cell-free DNA, in the context of organ transplantation ( 55 , 68 , 69 ). Caspase-1 leads to pyroptosis, a process of programmed cell death that includes cell swelling, membrane rupture, and release of cytosolic contents ( 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cell apoptosis-induced activation of inflammasomes is associated with cardiac allograft rejection ( 67 ). Caspase-1 activation is triggered by the assembly of inflammasome complexes, particularly Nlrp3, which function as sensors for ‘danger’ molecules or non-self signals, such as donor-derived cell-free DNA, in the context of organ transplantation ( 55 , 68 , 69 ). Caspase-1 leads to pyroptosis, a process of programmed cell death that includes cell swelling, membrane rupture, and release of cytosolic contents ( 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…We tested this hypothesis by examining the expression of related factors after NLRP3 inflammasome activation. NLRP3 inflammasomes regulate caspase-1 activation and promote the maturation and secretion of IL-1β during the natural immune defense ( Burke et al, 2021 ); they also regulate caspase-1-dependent programmed apoptosis and induce cell death under inflammatory and stressful pathological conditions ( Swanson et al, 2019 ). As shown in Figure 8 , we concluded that FA protects against I/R injury by inhibiting NLRP3 inflammasomes in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormally increased NLR in peripheral blood is a core indicator and mediator of systemic inflammation of any origin, including in COVID-19 [ 27 , 28 , 29 , 30 , 31 ]. Neutrophils, although essential for defense against infections, also participate in tissue destruction when their activity becomes overly exuberant, as occurs in human pathological inflammatory states for which dapsone is used such as bullous pemphigoid, Behcet’s disease, dermatitis herpetiformis, etc.…”
Section: Rationalementioning
confidence: 99%